2023
DOI: 10.1186/s13046-022-02560-6
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Linc00173 increases BCL2 mRNA stability via the miR-1275/PROCA1/ZFP36L2 axis and induces acquired cisplatin resistance of lung adenocarcinoma

Abstract: Background LINC00173 had been reported as a cisplatin (cis-diamminedichloroplatinum, DDP) chemotherapy-resistant inducer in small-cell lung cancer (SCLC) and lung squamous cell carcinoma (LUSC). This study aimed to display reverse data for LINC00173 as a DDP chemosensitivity-inducing factor in lung adenocarcinoma (LUAD). Methods LINC00173 was screened from the Gene Expression Omnibus database (GSE43493). The expression level of LINC00173 in LUAD ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…Using this dataset, we performed Kaplan-Meier analysis and found that the prognosis of the patient group with low LINC00173 expression, high SNAIL expression, and low FHIT expression was significantly poor (p = 0.0116, 0.0221, and 0.0074, respectively, Figure 4A). This is consistent with previous reports showing that LINC00173 and FHIT act as tumor suppressors in lung adenocarcinoma [8,46,52]. This dataset was then used for correlation analysis between the expression of these genes.…”
Section: Impact Of the Linc00173-snail-fhit Axis On Human Lung Adenoc...supporting
confidence: 87%
See 3 more Smart Citations
“…Using this dataset, we performed Kaplan-Meier analysis and found that the prognosis of the patient group with low LINC00173 expression, high SNAIL expression, and low FHIT expression was significantly poor (p = 0.0116, 0.0221, and 0.0074, respectively, Figure 4A). This is consistent with previous reports showing that LINC00173 and FHIT act as tumor suppressors in lung adenocarcinoma [8,46,52]. This dataset was then used for correlation analysis between the expression of these genes.…”
Section: Impact Of the Linc00173-snail-fhit Axis On Human Lung Adenoc...supporting
confidence: 87%
“…LINC00173 is associated with various types of human cancer in a cell context-dependent manner [7,9,10,46]. Among them, we focused on the non-small cell lung cancer, lung adenocarcinoma, in which LINC00173 acts as a suppressor of tumorigenesis and tumor progression [8,46]. We selected the A549 cell line derived from human lung adenocarcinoma for the analysis and obtained its expression profile under our culture conditions by RNA-seq.…”
Section: Lncrna Linc00173 Binds To Transcription Factor Snail In A549...mentioning
confidence: 99%
See 2 more Smart Citations
“…The development of DDP resistance impedes its application in cancer treatment. Previous studies have shown that lncRNAs may act as key targets in regulating DDP sensitivity (Chi et al., 2018; Tao et al., 2023; Zhang et al., 2019; Zhu et al., 2022). In present study, TCGA dataset and RT‐qPCR analyses showed that LINC00460 was highly expressed in cervical cancer tumor tissues and cell lines, and upregulation of LINC00460 might serve as a prognostic factor of cervical cancer patients.…”
Section: Discussionmentioning
confidence: 99%